Comprehensive Analysis of the Synergistic Effects of Bimetallic Oxides in CoM/γ-Al2O3 (M = Cu, Fe, or Ni) Catalysts for Enhancing Toluene Combustion Efficiency - Yuwei Tang; Xu Yang; Qinglong Zhang; Dongmei Lv; Shufeng Zuo; Jing Li (Molecules)
Catalytic combustion is an efficient and economic technology for eliminating volatile organic compounds (VOCs) in industrial environments. This study evaluated the synergistic catalytic properties of bimetallic oxides, viz., CoM/γ-Al2O3 (M = Cu, Fe, or Ni), for improving the combustion efficiency of toluene. The CoM/γ-Al2O3 catalysts were prepared by an impregnation method and characterized by using advanced techniques. Among the bimetallic catalysts, CoCu/γ-Al2O3 exhibited the best performance. The findings revealed that owing to the strong synergistic interaction between Cu, Co, and the γ-Al2O3 support, the active species in the CoCu/γ-Al2O3 catalyst were effectively stabilized, and they significantly enhanced the redox performance and acidity of the catalyst, demonstrating superior catalytic activity and sulfur resistance. Conversely, the CoFe/γ-Al2O3 catalyst performed poorly, exhibiting a significant decline in its activity owing to sulfur poisoning. The insights from this study provide theoretical support for designing efficient, sulfur-resistant catalysts that are crucial to reducing industrial VOC emissions.